2008
DOI: 10.1200/jco.2007.13.6028
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Oral Mucositis Audit: Oral Mucositis in Patients Receiving High-Dose Melphalan or BEAM Conditioning Chemotherapy—European Blood and Marrow Transplantation Mucositis Advisory Group

Abstract: Severe OM is more common in the transplantation setting than previously reported, justifying effective preventative and therapeutic measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
121
2
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(154 citation statements)
references
References 33 publications
14
121
2
12
Order By: Relevance
“…The first part of the analysis (described in our initial paper) revealed a high incidence of severe (World Health Organization (WHO) oral toxicity scale grade 3-4) 11 OM (44%) in patients with multiple myeloma (MM) or non-Hodgkin's lymphoma (NHL) who underwent high-dose dose melphalan or BEAM conditioning, respectively and autologous SCT. 1 Severe OM risk and/or duration were significantly associated with higher chemotherapy dose per kg body weight and poor performance status, but in contrast to some previous reports they were not related to age.…”
Section: Introductioncontrasting
confidence: 54%
See 4 more Smart Citations
“…The first part of the analysis (described in our initial paper) revealed a high incidence of severe (World Health Organization (WHO) oral toxicity scale grade 3-4) 11 OM (44%) in patients with multiple myeloma (MM) or non-Hodgkin's lymphoma (NHL) who underwent high-dose dose melphalan or BEAM conditioning, respectively and autologous SCT. 1 Severe OM risk and/or duration were significantly associated with higher chemotherapy dose per kg body weight and poor performance status, but in contrast to some previous reports they were not related to age.…”
Section: Introductioncontrasting
confidence: 54%
“…1 This second analysis of data from this pan-European audit provides new insights into the clinical sequelae of severe OM and associated medical resource use. Consistent with other observations, 8,13 we found that severe OM was closely related to development of fever, with the incidence of fever being 21% higher and the duration of fever 1.2 days longer, in those with severe OM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations